CROWDSOURCING-BASED MOBILE APPLICATION FOR SUPERMARKET STOCK AVAILABILITY CHECKER - MOHD RUSLI, AMIRAH WAHIDAH (IRC, 2020)
The need for a better shopping experience through search convenience is more than ever for shoppers of this generation who value time and effort. Hence, having found out that the item a shopper want is out of stock would be a devastating shopping experience. The purpose of this report is to describe the development of mobile application for supermarket stock availability checker which aims to address and provide solution for the aforementioned issue. This project is implementing spatial crowdsourcing technology in hope to optimize the frequent updates of the stock availability by means of contributions from users. Thus, this report details on the expectations of shopping experience from users, the spatial crowdsourcing algorithm used, and the testing conducted on this application.